2017
DOI: 10.4103/ijd.ijd_473_16
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous cysts with nail dystrophy in a young female: A classical association

Abstract: Pachyonychia Congenita (PC) refers to a group of autosomal dominant disorders with variable clinical presentations. While nail dystrophy and plantar keratoderma are the most consistent features in all the variants, a myriad of other manifestations has been observed. This report highlights a case of young female presenting with multiple asymptomatic cutaneous cysts associated with plantar kearatoderma and nail dystrophy. Similar nail changes were evident in her son also. Such clinical presentation, in corrobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The association of PC with HS has been described without genetic investigations in 5 out of 6 members of a family and that of PC‐1 with HS in a patient in which a heterozygous missense mutation in exon 7 of the KRT 6A gene has been reported . Interestingly, a unique genetic defect has been suggested as the likely explanation for the coexistence of SM and HS in two sisters and subsequent studies have identified KRT17 mutation as a genetic marker for both PC‐2 and familial SM . Mutations of this gene have also been found in HS and pilonidal cyst .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The association of PC with HS has been described without genetic investigations in 5 out of 6 members of a family and that of PC‐1 with HS in a patient in which a heterozygous missense mutation in exon 7 of the KRT 6A gene has been reported . Interestingly, a unique genetic defect has been suggested as the likely explanation for the coexistence of SM and HS in two sisters and subsequent studies have identified KRT17 mutation as a genetic marker for both PC‐2 and familial SM . Mutations of this gene have also been found in HS and pilonidal cyst .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are some reports on the association of SM with HS 16,17 as well as that of PC-2 with SM. [18][19][20] The association of PC with HS has been described without genetic investigations in 5 out of 6 members of a family 21 and that of PC-1 with HS in a patient in which a heterozygous missense mutation in exon 7 of the KRT 6A gene has been reported. 22 Interestingly, a unique genetic defect has been suggested as the likely Figure 2 Proband: on the trunk, multiple cutaneous lesions resulting from previous acne conglobata (a); on the right axilla, inflammatory lesions from HS (b); in the sacrococcygeal area, pilonidal cyst (circle) (c); on the scalp, some patches of cicatricial alopecia from dissecting cellulitis (d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations